Effects of Aqueous Extract of Cumin Seed (Cuminum cyminum) on the Structure and Function of Albino Rat Kidneys Treated with Dibutyl Phthalate - Alfahdawi, Othman Aeed Salih; Alfahdawi, Abdulrahman Aeed Salih; Mohammed, Israa Mahmood (Iraqi Journal of Science, 2023)
This study was aimed to investigate the effects of Cuminum cyminum seed aqueous extract on the function and histological structure of rat kidney treated with dibutyl phthalate (DBP). Eighteen albino rats weighing 190-240g and aged 10-12 weeks were used for this study which went on for 28 days. The rats were divided into three groups (each with six animals): 1st group: control rats were given food and tap water, 2nd group was given DBP (420mg/Kg. B.W.) with tap water and diet, 3rd group were fed cumin plant orally at a daily dose of (200 mg/kg B.W.) and DBP (420mg/kg. B.W.) was given with drinking water and fed with diet daily. Kidney and liver function parameters were measured and histological structure of kidney was examined. Results showed that DBP significantly increased creatinine, urea as well as liver parameters AST and ALT, while decreased ALP level, destruction, hemorrhage and inflammation in kidney. Cumin decreased AST and ALT level but increased ALP level and elevated kidney hemorrhage which concluded that DBP may cause oxidative stress for rat liver and kidney. Despite hepatoprotective role of cumin, it interacts with DPB and increases bleeding in kidney.